2005
DOI: 10.1063/1.1921340
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniformities of electrical resistivity in undoped 6H-SiC wafers

Abstract: Electrical and microstructural properties of highly boron-implantation doped 6H-SiCChemical elemental analysis, temperature-dependent Hall measurements, deep-level transient spectroscopy, and contactless resistivity mapping were performed on undoped semi-insulating ͑SI͒ and lightly nitrogen-doped conducting 6H-SiC crystals grown by physical vapor transport ͑PVT͒. Resistivity maps of commercial semi-insulating SiC wafers revealed resistivity variations across the wafers between one and two orders of magnitude. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…6. It can be seen that the concentrations of all of the deep traps related to Si-rich growth conditions [6,7] are strongly reduced with only the 0.4 eV trap remaining in any significant concentration.…”
Section: Effect Of H 2 and He On Crystal Growth And Impurity Incorpormentioning
confidence: 95%
See 1 more Smart Citation
“…6. It can be seen that the concentrations of all of the deep traps related to Si-rich growth conditions [6,7] are strongly reduced with only the 0.4 eV trap remaining in any significant concentration.…”
Section: Effect Of H 2 and He On Crystal Growth And Impurity Incorpormentioning
confidence: 95%
“…In SiC crystals grown by physical vapor transport, the absolute nitrogen concentration and the amount of its variation along the growth axis is determined by the changes in the effective C/Si ratio via the wellknown site competition effect [5]. As growth progresses, the ambient becomes more C-rich, which suppresses nitrogen incorporation into the C sites [6]. Concomitantly, the most prominent electron traps strongly decrease in concentration as the effective C/Si ratio increases suggesting that they are defects related to the Si-rich growth conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the yield of semi-insulating crystals depends on one's ability to reduce the concentration of shallow centers. In earlier publication, Li et al [4] have shown that nitrogen distribution along the growth axis in 6H-SiC boules is to a large extent determined by the effective C/Si ratio in the gas phase during growth. At the beginning of the PVT growth process, the growth ambient is typically highly Si-rich and changes to less Si-rich toward the end [5].…”
Section: Introductionmentioning
confidence: 98%
“…Since efficiency of nitrogen incorporation decreases with the C/Si ratio, its concentration is higher in the seed portion of the crystal compared to the tail portion. Concomitantly with change in nitrogen level, the concentrations of major deep electron traps decrease along the crystal growth axis [4,6]. These non-uniformities are inherent in PVT growth method and result in change of electrical properties both along the growth axis and across the boule diameter.…”
Section: Introductionmentioning
confidence: 98%
“…This process relies on sublimation and re-condensation of solid SiC, which experiences a significant drift in the C/Si ratio as the source material is consumed [1,2]. The changing stoichiometry leads to significant changes in material properties and doping concentrations both radially and axially in the crystal [3].…”
Section: Introductionmentioning
confidence: 99%